(untitled) (AmeriQuests, 2014)
The genre of travel literature in the nineteenth century, particularly in the francophone context, allowed European writers to compare the Old World with the New World and cast judgments about democracy, religion, and race in comparison to Europe, themes which are particularly relevant to our discussion about modernity. One such example of this literature is Outre-Mer by Paul Bourget which was written over an eight month period beginning in July 1893 and was published in Paris in 1895. Bourget is best known for his 1883 collection Essais de psychologie contemporaine and for his 1889 novel Le disciple. Although his work is viewed largely as minor literature today, in the 1880s and 1890s, he was essentially a literary celebrity. Thus, in 1893 when he visited Canada at the very beginning of his trip he was received with great fan fare and the events of his three-week vacation were chronicled in nearly every Francophone Quebec Journal. However, when the book was published in 1895, the Canadians were surprised to find that Bourget did not mention them once, as if he had never even gone to Canada. The outcry from the Canadian public, in my opinion, was not just about being snubbed by a literary celebrity, but showed that French-speaking Canadians genuinely wanted to hear Paul Bourget’s opinion about their culture and society. To meet this need, a Canadian journalist and editor named Sylva Clapin wrote Sensations de Nouvelle-France with the subtitle “Pour faire suite à Outre-Mer” and signed the book Paul Bourget. My communication seeks to study Sylva Clapin’s appropriation of Bourget’s political and social ideology which he used to create his forgery and launch a polemic in the francophone journals of Québec in 1895. At the core of Bourget’s vision is the concept that while Democracy, Science (Positivism), and the problems of Race were essentially destroying the Old World, they were at the heart of what made the Americas great. These are the tools that Clapin applied to his study of French-speaking Canada which I propose to explore in my communication.